Estudo clínico e epidemiológico dos pacientes internados com hemorragia digestiva alta no Hospital Universitário João de Barros Barreto - SILVA, Ariadne Fonseca Carvalho (2022)
The upper gastrointestinal bleeding is one of the most important problems in gastroenterology and a common indication for hospital admission, whose main symptoms include hematemesis, melena and/or rectal bleeding. Objectives: To perform a clinical and epidemiological study of patients admitted with upper gastrointestinal bleeding in the João de Barros Barreto University Hospital. Methods: It was conducted an epidemiological, observational, crosssectional and descriptive study, by analyzing medical records of 76 patients admitted with upper gastrointestinal bleeding in the João de Barros Barreto University Hospital (Brazil) in 2010, whose main aspects studied were demographic data, factors risk, clinical manifestations, classification of bleeding, established therapies, complications, hospitalization time and evolution. This project was approved by the Ethics Committee on Human Research. Results: In this sample, 59.2% were male (n=45), age between 38 and 57yearsold (42%, n=32), with a mean age of 54.9yearsold (18 to 92years old), Elementary Education (40.8%, n=31), and without record of family income (84.2%, n=64). Smoking was the main risk factor founded (26.34%, n = 54), while the previous use of NSAIDs/aspirin (6.3%, n=13) and infection by H. pylori (2.43%, n=5) were less frequent. Chronic liver diseases were the main comorbidities founded (40.7%, n=46), while Chronic Obstructive Pulmonary Disease was less frequent (0.9%, n=1). The main cause of bleeding was non variceal (70.4%, n=57), in which peptic ulcer (32.1%, n=26) was the most frequent. The Proton Pump Inhibitors were the drugs most prescribed for non variceal bleeding (46.7%, n=71), and the endoscopic band ligation was the main therapy instituted for variceal bleeding (70%, n = 13). Thirtynine patients (76.6%) evolved without complications and, when there were, they were represented by hypovolemic shock (7.8%, n=4), hepatic encephalopathy (7.8%, n=4) and rebleeding (7.8%, n=4). The average hospital stay was 2 to 3 weeks (47.3%, n=36), and the hospital discharge with improves was the main evolutionary outcome (53.9%, n=41). Conclusion: The epidemiological profile of participating patients were men, with mean age 54.9yearsold, and presented as main causes of upper gastrointestinal bleeding the peptic ulcer and the rupture of esophageal varices, reaching 25% mortality rate.